2016
DOI: 10.1186/s12893-016-0148-z
|View full text |Cite
|
Sign up to set email alerts
|

Total knee arthroplasty using trochlear groove as guide for position of femoral component in severe knee osteoarthritis

Abstract: BackgroundApart from transepicondylar axis, the native femoral sulcus was also reported to be used as a guide for the femoral component position in total knee arthroplasty (TKA). However, it was not shown in patients with severe knee osteoarthritis. This study was conducted to compare the position of trochlear groove in patients with and without osteoarthritis, and to assess whether trochlear groove could be used as a guide for position of femoral component in TKA for severe knee osteoarthritis.MethodsTotal 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Although new prosthesis and surgical instruments with more perfect design are constantly coming out, and the surgical technology of the operator is also improving year by year, TKA has not yet become a perfect operation, and its postoperative dissatisfaction rate is as high as 20% [ 39 , 40 ]. The main cause is that TKA has high requirements on the position of prosthesis placement, reconstruction of lower limb force line and maintenance of postoperative stability, while manual operation is difficult to ensure the accuracy and consistency of surgical operation [ [41] , [42] , [43] ]. Therefore, poor prosthesis position and poor alignment of lower limb occur from time to time, which seriously affects the stability of knee joint and recovery of motor function and the long-term survival rate and postoperative satisfaction of patients were reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Although new prosthesis and surgical instruments with more perfect design are constantly coming out, and the surgical technology of the operator is also improving year by year, TKA has not yet become a perfect operation, and its postoperative dissatisfaction rate is as high as 20% [ 39 , 40 ]. The main cause is that TKA has high requirements on the position of prosthesis placement, reconstruction of lower limb force line and maintenance of postoperative stability, while manual operation is difficult to ensure the accuracy and consistency of surgical operation [ [41] , [42] , [43] ]. Therefore, poor prosthesis position and poor alignment of lower limb occur from time to time, which seriously affects the stability of knee joint and recovery of motor function and the long-term survival rate and postoperative satisfaction of patients were reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the ATL, previous studies proposed the trochlear groove as an additional rotational landmark by stating that the native femoral sulcus could be used as a guide for the femoral component position in TKA surgery [8, 9, 27, 28]. Recently, Huang et al [13] confirmed this role of the native femoral sulcus in patients with severe osteoarthritis. In addition, Talbot et al [28] reported that the sulcus line of the trochlear groove is more accurate than Whiteside's line in determining femoral component rotation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] The preferred treatment option for treating such condition is knee joint replacement (KJR). [ 11 13 ] However, some patients still suffer from severe knee pain and poor quality of life after KJR. [ 14 , 15 ]…”
Section: Introductionmentioning
confidence: 99%